2010
DOI: 10.3858/emm.2010.42.9.064
|View full text |Cite
|
Sign up to set email alerts
|

Molecular imaging of membrane proteins and microfilaments using atomic force microscopy

Abstract: Atomic force microscopy (AFM) is an emerging technique for a variety of uses involving the analysis of cells. AFM is widely applied to obtain information about both cellular structural and subcellular events. In particular, a variety of investigations into membrane proteins and microfilaments were performed with AFM. Here, we introduce applications of AFM to molecular imaging of membrane proteins, and various approaches for observation and identification of intracellular microfilaments at the molecular level. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 72 publications
0
15
0
Order By: Relevance
“…Comparison with AFM, the resolution of fluorescence microscopy is lower, besides, the sample also need to fluorescent staining. However, AFM is reported that can be analyzed to get the parameters pertaining to the examined surface in a quantitative form at nanometer resolution (Jung et al , ). Although electron microscopy techniques such as transmission electron microscopy reaches nanometer and subnanometer resolution, the process of sample preparation needs complex and invasive treatments that could dramatically modify cell native structure (Tai and Tang, ; Daban, ).…”
Section: Introductionmentioning
confidence: 99%
“…Comparison with AFM, the resolution of fluorescence microscopy is lower, besides, the sample also need to fluorescent staining. However, AFM is reported that can be analyzed to get the parameters pertaining to the examined surface in a quantitative form at nanometer resolution (Jung et al , ). Although electron microscopy techniques such as transmission electron microscopy reaches nanometer and subnanometer resolution, the process of sample preparation needs complex and invasive treatments that could dramatically modify cell native structure (Tai and Tang, ; Daban, ).…”
Section: Introductionmentioning
confidence: 99%
“…Atomic force microscope (AFM) is a powerful tool for the characterization of biological sample. It can not only obtain the high-resolution images of cell morphology, membrane ultrastructure, and membrane proteins (Jung et al, 2010) but also measure mechanical properties of cell membrane, such as elasticity (Lekka and Laidler, 2009) and adhesion (Hosseini et al, 2009). In this study, HUVECs were plated and cultured on PLL-coated plate and FN-coated plate with or without celastrol treatment, and then morphology, cell surface roughness and cell mechanics were detected by AFM.…”
Section: Introductionmentioning
confidence: 99%
“…AFM images provide detailed morphological features such as size, shape and surface topography at sub-nanometer resolutions [54][55][56][57]. In addition, it provides information on cellular architectures such as structural, conformational, and constitutional information of cytoskeletal proteins and membrane lipids [58][59][60][61]. During pathological progression, cells often undergo morphological modulations.…”
Section: Morphologymentioning
confidence: 99%